2017
DOI: 10.1108/et-08-2016-0136
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of internship effectiveness in South Italy Universities

Abstract: Purpose The purpose of this paper is to describe and discuss the way internships are currently evaluated in Campania Universities by host institutions. Design/methodology/approach The author collected and described questionnaires used by the universities of the Regional Observatory of Campania University System. These questionnaires are given by the host institutions to interns to fill out, and they evaluate skills growth in terms of initial and final assessment. Data related to these questionnaires are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The content of "skills" is also something that can vary. Many studies mention cross-skills or general skills like critical thinking; problem solving; teamwork; IT or computer skills; or language and communication skills (Knouse and Fontenot, 2008;Dommeyer et al, 2016;della Volpe, 2017;Chen et al, 2018;Marks et al, 2018;Kapareliotis et al, 2019). Some studies have highlighted professional skills (della Volpe, 2017; Chen et al, 2018;Nghia and Duyen, 2018;Anjum, 2020), referring to skills that are specific to a certain profession.…”
Section: Internship Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…The content of "skills" is also something that can vary. Many studies mention cross-skills or general skills like critical thinking; problem solving; teamwork; IT or computer skills; or language and communication skills (Knouse and Fontenot, 2008;Dommeyer et al, 2016;della Volpe, 2017;Chen et al, 2018;Marks et al, 2018;Kapareliotis et al, 2019). Some studies have highlighted professional skills (della Volpe, 2017; Chen et al, 2018;Nghia and Duyen, 2018;Anjum, 2020), referring to skills that are specific to a certain profession.…”
Section: Internship Outcomesmentioning
confidence: 99%
“…(2019) found that classroom preparation does not affect the perceived value of an internship. Some studies have revealed that there are different perceptions about the preparation or characteristics of internship students; companies expect more autonomous students (della Volpe, 2017). The study by Jackling and Natoli (2015) about international student internships in Australia demonstrated that communication skills and awareness of relevant business culture were not up to the level expected by companies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations